Size, shape, charge and "stealthy" surface: Carrier properties affect the drug circulation time in vivo - Jinwei Di; Xiang Gao; Yimeng Du; Hui Zhang; Jing Gao; Aiping Zheng (Elsevier, 2021)
The present review sets out to discuss recent developments of the effects and mechanisms of carrier properties on their circulation time. For most drugs, sufficient in vivo circulation time is the basis of high bioavailability. Drug carrier plays an irreplaceable role in helping drug avoid being quickly recognized and cleared by mononuclear phagocyte system, to give drug enough time to arrive at targeted organ and tissue to play its therapeutic effect. The physical and chemical properties of drug carriers, such as size, shape, surface charge and surface modification, would affect their in vivo circulation time, metabolic behavior and biodistribution. The final circulation time of carriers is determined by the balance between macrophage recognitions, blood vessel penetration and urine excretion. Therefore, when designing the drug delivery system, we should pay much attention to the properties of drug carriers to get enough in vivo circulation time to arrive at target site eventually. This article mainly reviews the effect of carrier size, size, surface charge and surface properties on its circulation time in vivo, and discusses the mechanism of these properties affecting circulation time. This review has reference significance for the research of long-circulation drug delivery system.